The Influence of Competence and Work Environment on Employee Performance at the Office of Industry and Trade of South Tangerang City - Ajeng Eka Wulandary; Cecep Haryoto (MES Management Journal, 2025)
This study aims to analyze the effect of competence and work environment on employee performance at the Office of Industry and Trade of South Tangerang City using a quantitative approach. Data were collected through questionnaires distributed to 60 employees and analyzed using multiple linear regression with SPSS. The results show that competence has a positive and significant effect on employee performance, as indicated by a t-value of 7.434 with a significance level below 0.05, suggesting that employees’ knowledge, skills, and work attitudes contribute to improved performance. The work environment also has a positive and significant influence on employee performance, with a t-value of 6.001 and a significance level below 0.05, indicating that a conducive work environment enhances employee productivity. Simultaneously, competence and work environment have a positive and significant effect on employee performance, as evidenced by an F-value of 89.966 with a significance level below 0.05, implying that optimal employee performance is achieved through both individual competence and a supportive work environment.